RIDDLE GAMES TO ENHANCE VOCABULARY MASTERY - Imroatin Octaviarnis (Fakultas Ilmu Budaya, Universitas Brawijaya, 2020)
Vocabulary is an essential part in learning English. The common problems in learning English might be caused of the students were lack of vocabulary. The aimed of the study was to solve the problems by using riddles game. The researcher used Classroom Action Research as the research design. There were four stages in one cycle in which planning the action, implementing the action, observing the action, and reflecting on the action. One cycle of this research that consisted of three meetings. The subject of the study was 7 H class. The researcher used the research instruments such as interview guide, questionnaire, observation checklist, field notes and test. The criterion of success in which 70% of the students passed the minimum score that was 80. The average score of post-test was 93,54% students passed the criterion of success. Based on the post questionnaire, the students felt interested during learning process and the students’ vocabulary mastery was improved. The researcher suggested to English teacher to use riddles game as an alternative technique in teaching vocabulary, to students could apply this game out of the class, and the researcher hopes other researchers can use riddles game as a reference to conduct their research on the field because riddles game is the effective way to teach vocabulary.